Utility of hypoxic modalities for musculoskeletal injury rehabilitation in athletes: a narrative review of mechanisms and contemporary perspectives - Narang, B. J.; Drole, K.; Barber, J. F. P.; Goods, P. S. R.; Debevec, T. (Journal of Sports Sciences, 2025)
Recent evidence suggests that different hypoxic modalities might accelerate the rehabilitation process in injured athletes. In this review, the application of hypoxia during rehabilitation from musculoskeletal injury is explored in relation to two principles: (1) facilitating the healing of damaged tissue, and (2) mitigating detraining and inducing training adaptations with a reduced training load. Key literature that explores the underlying mechanisms for these themes is presented, and considerations for practice and future research directions are outlined. For principle (1), passive intermittent hypoxic exposures might accelerate tissue healing through angiogenic and osteogenic mechanisms. Experimental evidence is largely derived from rodent research, so further work is warranted to establish whether clinically meaningful effects can be observed in humans, before optimal protocols are determined (duration, frequency, and hypoxic severity). Regarding principle (2), a hypoxia-related increase in the cardiometabolic stimulus imposed by low-load exercise is appealing for load-compromised athletes. As rehabilitation progresses, a variety of hypoxic modalities can be implemented to enhance adaptation to energy-systems and resistance-based training, and more efficiently return the athlete to competition readiness. While hypoxic modalities seem promising for accelerating musculoskeletal injury rehabilitation in humans, and are already being widely used in practice, a significant gap remains regarding their evidence-based application.